2022
DOI: 10.3390/educsci13010034
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors’ Perspectives on Online Interprofessional Supervision: Results from a Mixed-Methods Longitudinal Cross-Sectional Study

Abstract: Collaboration in interprofessional collaboration (IPC) teams is a part of working in welfare services. Unlike uniprofessional supervision, interprofessional supervision involves supervisors and students with different educational backgrounds. This study explores 105 supervisors’ responses after synchronous supervision of 15,700 students from teaching, health, and social work education programs who participated in an annual preservice interprofessional learning (IPL) course from 2018 to 2022. The purpose was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Pirani et al (2022) reported that interprofessional simulation across health and education improved students' ability with communication, conflict resolution, and collaboration to increase students' confidence to work in partnerships. Almendingen et al (2022) further support the benefit of IPE across health, social care and education identifying as previously acknowledged that students were able to learn with, from, and about each other. However, the research projects used digital online platforms and, therefore, further research is needed to compare if oncampus delivery impacts the learning achieved.…”
Section: Evidence On the Design Development And Delivery Of Interprof...supporting
confidence: 59%
See 2 more Smart Citations
“…Pirani et al (2022) reported that interprofessional simulation across health and education improved students' ability with communication, conflict resolution, and collaboration to increase students' confidence to work in partnerships. Almendingen et al (2022) further support the benefit of IPE across health, social care and education identifying as previously acknowledged that students were able to learn with, from, and about each other. However, the research projects used digital online platforms and, therefore, further research is needed to compare if oncampus delivery impacts the learning achieved.…”
Section: Evidence On the Design Development And Delivery Of Interprof...supporting
confidence: 59%
“…Following simulation, learners need to understand how the theoretical knowledge gained can be applied to professional practice. Hence, Almendingen et al (2022) point out that the success of IPE is dependent on students' perspectives regarding the relevance and realism of the topics. Therefore, it is important for the session to be designed and tailored to support the needs of all the students in attendance at the event, this was completed by the professional disciplines who organised the event by structuring the aims, learning outcomes and designing bespoke resources to meet the students' learning needs.…”
Section: The Design and Development Of The Resources Used Within Simu...mentioning
confidence: 99%
See 1 more Smart Citation
“…After feedback from students, stakeholders, and in response to the results of the pre-pandemic studies, the educational activities and content were adjusted along the way [56,58,59,67]; however, the course description and the major tasks remained unchanged.…”
Section: Ipl Coursementioning
confidence: 99%
“…The authors highlighted potential management challenges such as providing essential technological support and skills development for remote workers (Quade, 2022). To address these kinds of challenges, literature from other scholars of telework recommended collaboration between virtual teams and supervisors through communication mediums as a driving force for achieving project goals (Almendingen, Skotheim, & Magnus, 2023).…”
Section: People Factorsmentioning
confidence: 99%